Homoconjugation and intramolecular charge transfer in extended aromatic triptycenes with different π-planes - Baumgärtner, Kevin; Hoffmann, Marvin; Rominger, Frank; Elbert, Sven; Dreuw, Andreas; Mastalerz, Michael (The journal of organic chemistry, 2020)
Homoconjugation and intramolecular “through-space” charge transfers are molecular phenomena that have been studied since the 1960s. A detailed understanding and control of these effects would provide a tool to tune the optoelectronic properties of organic molecules in respect of the necessities for applications such as for organic electronics. Triptycene is a perfect candidate to investigate homoconjugation effects due to its three-dimensional alignment of three aromatic phenylene units, separated by two methine bridges. Here, a series of 16 π-extended triptycenes with up to three different permuted electron-accepting units and an electron-rich veratrole unit are studied in detail by UV/vis spectroscopy and cyclovoltammetry in combination with DFT calculations to get a deeper understanding of homoconjugation and charge-transfer processes of triptycenes. Furthermore, the gained knowledge can be exploited to construct triptycene-based electron acceptors with fine-tuned adjustment of electronic properties, such as electron affinities, by thorough choice of the aromatic blades that interact through homoconjugation.
Gesehen am 13.02.2022